1999
DOI: 10.1017/s1367943099000608
|View full text |Cite
|
Sign up to set email alerts
|

Use of genetic data for conservation management: the case of the Arabian oryx

Abstract: In this study we investigate some applications of genetic markers in animal conservation, using the Arabian oryx (Oryx leucoryx) as an example. Out of 66 sets of microsatellite primers from other ruminants, 58% were found to amplify microsatellites in Arabian oryx. Polymorphism (50% of loci amplified) and allelic diversity (mean 2.1 alleles/locus amplified) were within the range found in other ruminants. Arabian oryx (n = 343) representing most of the major groups world-wide were typed at six loci. Low but sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 28 publications
1
43
2
3
Order By: Relevance
“…However, in a recent study, we have observed some rare alleles (genotypes) in Arabian oryx population using microsatellite markers (Arif et al, 2010). Marshall et al (1999) have also reported deficiencies of rare alleles in two of the four contemporary populations of Arabian oryx. The phenotypic characteristic (e.g.…”
Section: T G a G A T G C T ----Agc --C --------T -----A ---T -----Agcmentioning
confidence: 65%
“…However, in a recent study, we have observed some rare alleles (genotypes) in Arabian oryx population using microsatellite markers (Arif et al, 2010). Marshall et al (1999) have also reported deficiencies of rare alleles in two of the four contemporary populations of Arabian oryx. The phenotypic characteristic (e.g.…”
Section: T G a G A T G C T ----Agc --C --------T -----A ---T -----Agcmentioning
confidence: 65%
“…However, previous molecular studies have found errors in studbooks (e.g. Waldrapp ibis (Signer et al, 1994), Bali starling (Ashworth and Parkin, 1992) and Arabian oryx (Marshall et al, 1999)) meaning that it is probable that some of the pedigrees analysed here contained errors.…”
Section: Statistical Performance Of the Modelsmentioning
confidence: 82%
“…The two groups of investigators have used the same set of 6 microsatellite loci, 5 of them specific to sheep and 1 to cattle, for measuring the molecular diversity of Arabian oryx (Marshall et al 1999) and scimitar-horned oryx (Iyengar et al 2007). In the present study, we have applied 7 microsatellite markers, one of them (RBP3) is common to the previous studies on oryx (Marshall et al, 1999;Iyengar et al, 2007) whereas the remaining 6 loci have recently been utilized for measuring the genetic diversity of Tibetan antelope (Zhou et al, 2007). None of the loci in our study showed significant deviation from Hardy-Weinberg equilibrium (Table 2).…”
Section: Discussionmentioning
confidence: 99%